Rituximab in Systemic Lupus Erythematosus: Transient Effects on Autoimmunity Associated Lymphocyte Phenotypes and Implications for Immunogenicity - Faustini, Francesca; Sippl, Natalie; Stålesen, Ragnhild; Chemin, Karine; Dunn, Nicky; Fogdell-Hahn, Anna; Gunnarsson, Iva; Malmström, Vivianne (Frontiers in Immunology, 2022)
B cell abnormalities are common in systemic lupus erythematosus (SLE), and include expansion of double negative (DN) and age-associated-like B cells (ABC-like). We aimed to investigate rituximab (RTX) effects on DN and ABC-like B-cell subsets and, when possible, also secondary effects on T cells. Fifteen SLE patients, fulfilling the ACR 1982 criteria, starting RTX and followed longitudinally up to two years, were analyzed for B- and T- lymphocyte subsets using multicolor flow cytometry. DN were defined as IgD-CD27- and ABC-like as CD11c+CD21- within the DN gate. Additional phenotyping was performed adding CXCR5 in the B-cell panel. Cellular changes were further analyzed in the context of anti-drug antibodies (ADA) generation and clinical information. The SLE patients were mainly females (86.6%), of median age 36.7 (29.8-49.4) years and disease duration of 6.1 (1.6-11.8) years. Within the DN subset, ABC-like (IgD-CD27-CD11c+CD21-) B cell frequency reduced from baseline median level of 20.4% to 11.3% (p=0.03), at early follow-up. The DN B cells were further subdivided based on CXCR5 expression. Significant shifts were observed at the early follow-up in the DN2 sub-cluster (CD11c+CXCR5-), which reduced significantly (-15.4 percentage points, p=0.02) and in the recently described DN3 (CD11c-CXCR5-) which increased (+13 percentage points, p=0.03). SLE patients treated with RTX are at high risk of developing ADA. In our cohort, the presence of ADA at 6 months was associated with lower frequencies of DN cells and to a more pronounced expansion of plasmablasts at early follow-up. The frequency of follicular helper T cells (TFH, CD4+PD-1+CXCR5+) and of peripheral helper T cells (TPH, CD4+PD-1+CXCR5-) did not change after RTX. A sub-cluster of PD-1highCD4+ T cells showed a significant decrease at later follow-up compared to early follow-up (p=0.0039). It is well appreciated that RTX transiently influences B cells. Here, we extend these observations to cell phenotypes which contribute directly to autoimmunity in SLE. We show early transient effects of RTX on ABC-like memory B cells, later effects on PD-1high CD4+ cells, and possible implications for RTX immunogenicity. Further insight in such effects and their monitoring may be of clinical relevance.